Preparation method and preparation system of antibacterial flame-retardant lyocell fiber
Patent Information
- Application Number
- CN202411370722.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-02-14
AI Technical Summary
In the existing preparation method for flame retardant lyceler fibers, the flame retardant used is chemically toxic, affects the biocompatibility of the fibers, and produces harmful gases in the event of a fire. In addition, Lycel fibers are prone to propagation of bacteria and fungi, limiting its application in the fields of high-end home textiles and women's clothing.
The lycel fibers are coated by the introduction of chitosan and sodium alginate to form an antibacterial and flame retardant layer. The electrostatic interaction between chitosan and sodium alginate enhances the adhesion of the flame retardant layer and improves the water-washing resistance of the fiber.
It gives Lycel fiber excellent antibacterial and flame retardant properties, maintains the biocompatibility of the fiber, and provides a wider application prospect in the textile field.
Smart Images

Figure CN119433979A_ABST
Abstract
Description
Technical Field
[0001] The invention specifically relates to a preparation method and a preparation system of antibacterial and flame-retardant lyocell fibers, and belongs to the technical field of functionalized cellulose regenerated fibers. Background Art
[0002] Lyocell fiber is known as the "green fiber" of the 21st century. It is a new type of regenerated cellulose fiber produced by physical dissolution and regeneration. The entire production process is green and pollution-free. As a new type of textile fabric, Lyocell fiber combines the excellent properties of natural fibers and synthetic fibers. It not only has mechanical properties comparable to chemical fibers, but also has the comfort and touch of cotton fibers and silk. It is widely used in the textile field. Lyocell fiber, like other regenerated cellulose fibers, is a flammable material. Its textiles are also extremely flammable and can easily cause fires. Therefore, the development of flame-retardant Lyocell fiber is crucial for the application of Lyocell fiber in the textile field.
[0003] At present, the preparation of flame-retardant lyocell fiber mainly combines halogen, phosphorus, silicon, nitrogen and other flame retardants with lyocell fiber through blending, graft copolymerization and finishing. However, most of these flame retardants have certain chemical toxicity, which will not only reduce the excellent biocompatibility of lyocell fiber, but also cause certain environmental pressure in production. Moreover, although the flame-retardant lyocell fiber prepared by these flame retardants can achieve the flame retardant effect, it will produce harmful and unpleasant gases, which will cause harm to the human body. In addition, lyocell fiber, like other synthetic fibers, is easy to breed bacteria and fungi, and its application in the field of high-end home textiles and high-end women's clothing will be subject to certain restrictions. If lyocell fiber can be given antibacterial and flame retardant properties at the same time, then lyocell fiber will be more widely used in the textile field.
[0004] Although the prior art CN112410931A discloses "a sodium alginate / chitosan composite fiber and its preparation method and application", its materials are derived from biopolysaccharides, that is, quaternized chitosan and sodium alginate are used as raw materials to prepare a new sodium alginate / chitosan (SA / HACC) composite fiber. CN109162096A discloses "a method for preparing flame-retardant Lyocell cellulose fiber based on post-treatment method", wherein Lyocell fiber tow is treated, alginate is added to the coagulation bath, and metal cations are added during the washing process for curing, thereby giving the Lyocell fiber flame retardant properties; however, the addition of alginate in the coagulation bath will greatly affect the recovery of the solvent NMMO in the Lyocell fiber production process, causing solvent loss and increasing production costs; in addition, the addition of metal cations during the washing process will pollute the washing system and bring certain troubles to sewage treatment. CN109440450A discloses "a method for preparing durable antibacterial cellulose fibers", which mainly uses an antibacterial working solution to post-finish the fibers, and the antibacterial working solution includes an antibacterial agent, an alkaline auxiliary agent and a penetrant; however, the antibacterial agent used in this method is a metal magnesium salt, a metal copper salt and a metal zinc salt, etc. Although the obtained fibers have good antibacterial effects, the introduction of metal salts will reduce the original biocompatibility of the fibers, which may pose potential safety hazards to the human body, and its application in the textile field will be greatly restricted, etc. Summary of the invention
[0005] In order to effectively solve the problems of the prior art, a preparation method and a preparation system of antibacterial and flame-retardant lyocell fiber are proposed. Firstly, lyocell fiber (short fiber, with specific hydrophilicity, etc.) is used as the base material, and chitosan is introduced to coat the lyocell fiber, so that the regenerated chitosan is wrapped on the surface of the lyocell fiber to form an antibacterial layer; secondly, sodium alginate is introduced to coat the lyocell fiber that has formed an antibacterial layer, so that the regenerated sodium alginate is wrapped on the surface of the lyocell fiber to form a flame-retardant layer; finally, antibacterial and flame-retardant lyocell fiber is obtained. This method can not only give lyocell fiber excellent antibacterial properties, but also give lyocell fiber good flame-retardant properties; at the same time, the electrostatic interaction between chitosan and sodium alginate further strengthens the adhesion of the flame-retardant layer, improves the water washing resistance of the functional fiber, and weakens the effect of water washing on the antibacterial and flame-retardant properties of the functional fiber;
[0006] In addition, the chitosan and sodium alginate raw materials used in the present invention are both natural polymers, which can retain the good biocompatibility of the lyocell fiber itself to a great extent. Moreover, the preparation method proposed in the present invention is mainly based on the post-treatment of the lyocell fiber, and does not affect the production process of the lyocell fiber itself, which is greatly different from the preparation of the existing functional spinning solution, that is, the preparation method has great industrial application prospects.
[0007] In order to achieve the above technical objectives, the following technical solutions are proposed:
[0008] The first purpose of the technical solution is to provide a method for preparing antibacterial flame-retardant lyocell fiber, comprising the following steps:
[0009] 1) Preparation of Lyocell Fiber
[0010] The cellulose pulp is crushed and dissolved in an aqueous solution of N-methylmorpholine-N-oxide (NMMO) to form a cellulose solution with a concentration of 12.0 to 14.0 wt %; then, the cellulose solution is filtered and a lyocell fiber tow is obtained by dry-jet wet spinning;
[0011] The obtained lyocell fiber tow is washed with water, cut, and the lyocell fiber (short fiber) having a length of 30 to 60 mm, a dry breaking strength of ≥4.5 cN / dtex, and a dry breaking elongation of ≥18% is obtained;
[0012] Among them, in the preparation process of lyocell fiber, the higher the concentration of cellulose solution, the better the strength of the obtained fiber, and the production efficiency will be correspondingly improved, which is conducive to reducing costs. However, at present, due to the limited solubility of the solvent, if you want to achieve a higher cellulose concentration, you can only reduce the degree of polymerization of the pulp raw material, but this will affect the performance indicators of the fiber and also affect the production efficiency. For this reason, the present invention controls the formation of a cellulose solution with a concentration of 12.0-14.0wt%, effectively ensuring the performance indicators of the fiber, while ensuring production efficiency and avoiding an increase in production costs, such as: below this concentration, the fiber performance decreases, the production efficiency decreases, and the production cost increases;
[0013] Lyocell fibers can be purchased directly from the market or prepared by yourself. In principle, the higher the performance index of the short fiber, the better, which can better guarantee the performance of the subsequent functional fiber, but the comprehensive cost, preparation efficiency and processing conditions (such as: the coating of the flame retardant layer and the antibacterial layer will cause the performance index of the fiber to decline to varying degrees). Finally, the present invention selects the initial fiber with dry breaking strength ≥4.5cN / dtex and dry breaking elongation ≥18%, which is not only better adapted to the subsequent coating process, but also ensures the quality of the final product - antibacterial flame retardant Lyocell fiber;
[0014] Here, the length of lyocell fiber is limited to 30-60mm, and the specific specifications are determined according to actual needs. For example, the length specification of lyocell staple fiber products is 38mm or 42mm;
[0015] 2) Pre-treatment: laying nets, dehydration
[0016] The obtained lyocell fibers are evenly spread on a conveyor mesh belt, and then the lyocell fibers are squeezed and dehydrated by a pressing roller to obtain lyocell fibers with a water content of 30 to 50%;
[0017] Among them, dehydration is mainly to deal with the residual water in the washing process during the preparation of Lyocell fiber, to prevent excessive residual water in the Lyocell fiber when the chitosan solution is sprayed later, which will significantly dilute the concentration of the chitosan solution and affect the spraying effect. To this end, under the premise of limited squeezing capacity of the existing roller equipment, in order to reduce the influence of the water content of Lyocell fiber on the spraying effect of the chitosan solution, the water content of Lyocell fiber is controlled to be 30-50%;
[0018] 3) Spraying and squeezing of chitosan solution
[0019] A chitosan solution with a concentration of 0.5-2.0 wt% and a temperature of 20-50° C. is added to a chitosan solution spraying device to spray the lyocell fibers on the conveyor belt; then, a pressing roller is used to squeeze the lyocell fibers to remove the unabsorbed chitosan (the chitosan solution squeezed by the pressing roller is recovered and recycled through a receiving tank), and the chitosan solution content of the lyocell fibers is controlled to be 50-60%;
[0020] Among them, since the chitosan solution is a polymer solution with a certain viscosity, if the concentration of the chitosan solution is too high, the viscosity of the chitosan solution is too high, resulting in poor fluidity of the chitosan solution, which will not only affect the spraying effect on the lyocell fiber, but also have a certain impact on the spraying equipment; if the concentration of the chitosan solution is too low, although the chitosan solution has better fluidity, the chitosan content wrapped on the surface of the lyocell fiber will be reduced, which will affect the antibacterial properties of the final product. In addition, temperature affects the viscosity of the chitosan solution, that is, the higher the temperature, the lower the viscosity of the chitosan solution, the better the fluidity, and the better the spraying effect on the lyocell fiber, but if the temperature is too high, it will cause the chitosan to decompose; if the temperature is too low, the viscosity of the chitosan solution becomes higher, the fluidity becomes worse, and the spraying effect on the lyocell fiber will also become worse; therefore, in order to ensure the antibacterial properties of the final product, improve preparation efficiency, reduce production costs, and extend the service life of the equipment, a chitosan solution with a concentration of 0.5-2.0wt% and a temperature of 20-50°C is used;
[0021] In addition, “controlling the lyocell fiber to have a chitosan solution content of 50-60%” is mainly to cooperate with the next process (regeneration reaction of chitosan and NaOH), for example: if there is too much chitosan solution remaining on the surface of the lyocell fiber, then the chitosan layer wrapped on the surface of the lyocell fiber will not only become thicker, but also cause the thickness of the wrapped chitosan layer to be uneven, seriously affecting the uniformity of the final thickness of the lyocell fiber; if the chitosan solution remaining on the surface of the lyocell fiber is too low, then the chitosan layer will not wrap the lyocell fiber sufficiently, resulting in a decrease in the antibacterial performance of the lyocell fiber and uneven distribution. For this reason, the lyocell fiber is controlled to have a chitosan solution content of 50-60%;
[0022] 4) NaOH solution spraying and squeezing
[0023] A NaOH solution with a concentration of 0.1-1.0 wt% and a temperature of 20-30° C. is added to a NaOH solution spraying device to spray the lyocell fibers on the conveyor belt; then, a pressing roller is used to squeeze the lyocell fibers to remove unreacted NaOH (the NaOH solution squeezed by the pressing roller is recovered and recycled through a receiving tank), and the NaOH solution content is controlled to be 30-50% of the lyocell fibers;
[0024] The NaOH solution solidifies the chitosan solution wrapped on the surface of the lyocell fiber and forms an antibacterial layer on the surface of the lyocell fiber. When the chitosan solution is in the acid solution, the amino groups on the molecular chain will be protonated to form -NH3 + Ions dissolve due to electrostatic repulsion, so a base is used to neutralize -NH3 + ions, deprotonating the amino group and turning it back into -NH2, which precipitates and solidifies from the solution. Other alkalis can be used instead of NaOH solution, but different alkalis will affect the solidification rate of the chitosan solution. If the concentration of NaOH solution is too high, the chitosan regeneration rate will be too fast, which may easily lead to sticking between Lyocell fibers; if the concentration is too low, the chitosan regeneration rate will be too slow, and a stable chitosan layer cannot be formed on the surface of the Lyocell fiber. In addition, temperature affects the solidification rate of the chitosan solution. If the temperature is too low, the solidification rate will be too slow, and a stable chitosan layer cannot be formed on the surface of the Lyocell fiber; if the temperature is too high, the solidification rate will be too fast, causing the Lyocell fiber to become sticky. For this reason, a NaOH solution with a concentration of 0.1-1.0wt% and a temperature of 20-30°C is used;
[0025] In addition, the next step is to wash with water to remove the NaOH on the surface of the Lyocell fiber. Therefore, the residual NaOH solution on the surface of the Lyocell fiber should be removed as much as possible before washing with water, so as to ensure that the NaOH can be fully removed in the subsequent washing. However, under the premise of the limited extrusion capacity of the existing roller equipment, the NaOH solution content of the Lyocell fiber is controlled to be 30-50%;
[0026] 5) Washing and dehydration
[0027] The lyocell fibers on the conveyor belt are sprayed with water by the water spray device I, that is, the lyocell fibers are washed with water to remove the unreacted NaOH remaining on the surface of the lyocell fibers; then, the lyocell fibers are squeezed and dehydrated to obtain lyocell fibers with a water content of 30 to 50%;
[0028] Among them, in order to better cooperate with the subsequent sodium alginate solution spraying process, the water content of the lyocell fiber is controlled to be 30-50%. If there is too much residual water in the lyocell fiber, the concentration of the sodium alginate solution will be significantly diluted, thereby affecting the spraying effect. To this end, under the premise that the extrusion capacity of the existing roller equipment is limited, in order to reduce the influence of the water content of the lyocell fiber on the spraying effect of the sodium alginate solution, the water content of the lyocell fiber is controlled to be 30-50%;
[0029] 6) Sodium alginate solution spraying and squeezing
[0030] A sodium alginate solution with a concentration of 0.5-2.0 wt% and a temperature of 40-50° C. is added to a sodium alginate solution spraying device to spray the lyocell fibers on the conveyor belt; then, a pressing roller is used to squeeze the lyocell fibers to remove the unabsorbed sodium alginate (the sodium alginate solution squeezed by the pressing roller is recovered and recycled through a receiving tank), and the lyocell fibers with a sodium alginate solution content of 50-60% are obtained;
[0031] Among them, similarly, since the sodium alginate solution is a polymer solution with a certain viscosity, if the concentration of the sodium alginate solution is too high, the viscosity of the sodium alginate solution is too high, resulting in poor fluidity of the sodium alginate solution, which will not only affect the spraying effect on the lyocell fiber, but also have a certain impact on the spraying equipment; if the concentration of the sodium alginate solution is too low, although the fluidity of the sodium alginate solution is better, the content of sodium alginate wrapped on the surface of the lyocell fiber will be reduced, which will affect the flame retardant properties of the final product. Furthermore, temperature affects the viscosity of the sodium alginate solution, that is, the higher the temperature, the lower the viscosity of the sodium alginate solution, the better the fluidity, and the better the spraying effect on the lyocell fiber. However, if the temperature is too high, the sodium alginate will decompose; if the temperature is too low, the viscosity of the sodium alginate solution will increase, the fluidity will deteriorate, and the spraying effect on the lyocell fiber will also deteriorate. Therefore, in order to ensure the flame retardant properties of the final product, improve the preparation efficiency, reduce the production cost, and extend the service life of the equipment, a sodium alginate solution with a concentration of 0.5-2.0wt% and a temperature of 40-50°C is used;
[0032] In addition, “controlling to obtain Lyocell fiber with a sodium alginate solution content of 50-60%” is mainly to cooperate with the next process (regeneration reaction of chitosan and CaCl2), just as: if there is too much sodium alginate solution remaining on the surface of Lyocell fiber, then the sodium alginate layer wrapped on the surface of Lyocell fiber will not only become thicker, but also cause the thickness of the wrapped sodium alginate layer to be uneven, seriously affecting the uniformity of the final thickness of Lyocell fiber; if the sodium alginate solution remaining on the surface of Lyocell fiber is too low, then it will cause the sodium alginate layer to wrap the Lyocell fiber insufficiently, resulting in the decrease of flame retardant performance of Lyocell fiber and uneven distribution. For this reason, the sodium alginate solution content of 50-60% Lyocell fiber is controlled;
[0033] 7) CaCl2 solution spraying and squeezing
[0034] A CaCl2 solution with a concentration of 0.1-1.0 wt% and a temperature of 20-30° C. is added to a CaCl2 solution spraying device to spray the lyocell fibers on the conveyor belt; then, a pressing roller is used to squeeze the lyocell fibers to remove unreacted CaCl2 (the CaCl2 solution squeezed by the pressing roller is recovered and recycled through a receiving tank), and the CaCl2 solution content is controlled to be 30-50% of the lyocell fibers;
[0035] Among them, the concentration of CaCl2 is limited mainly to control the regeneration rate of sodium alginate. If the concentration of CaCl2 is too high, the sodium alginate solution will solidify too quickly, which will easily cause the Lyocell fibers to stick together; if the concentration is too low, the sodium alginate regeneration rate will be too slow, and a stable sodium alginate layer cannot be formed on the surface of the Lyocell fiber. The temperature of CaCl2 is also limited to control the solidification rate of the sodium alginate solution. For example: if the temperature is too low, the solidification rate will be too slow, and a stable sodium alginate layer cannot be formed on the surface of the Lyocell fiber; if the temperature is too high, the gelation rate will be too fast, causing the Lyocell fiber to stick. For this reason, a CaCl2 solution with a concentration of 0.1-1.0wt% and a temperature of 20-30°C is used. For the cross-linking agent, in addition to the CaCl2 solution, MgCl2 solution or FeCl3 solution can also be used, but based on cost, impact on the human body and other considerations, CaCl2 solution is preferred as the cross-linking agent;
[0036] In addition, the next step is to wash and remove the CaCl2 on the surface of the Lyocell fiber. Therefore, the residual CaCl2 solution on the surface of the Lyocell fiber should be removed as much as possible before washing, so as to ensure that the CaCl2 can be fully removed in the subsequent washing. However, under the premise of the limited squeezing capacity of the existing roller equipment, the CaCl2 solution content of the Lyocell fiber is controlled to be 30-50%;
[0037] 8) Post-treatment: Wash with water
[0038] The lyocell fibers on the conveyor belt are sprayed by the water spray device II, that is, the lyocell fibers are washed with water to remove the unreacted CaCl2 remaining on the surface of the lyocell fibers; then, the lyocell fibers are squeezed and dehydrated to obtain lyocell fibers with a water content of 30-50%, that is, the antibacterial and flame-retardant lyocell fibers;
[0039] The washing temperature is 20-30° C. In addition, in order to better cooperate with the post-treatment process of the antibacterial and flame-retardant lyocell fiber, such as oiling and drying, the water content of the lyocell fiber is controlled to be 30-50%.
[0040] Furthermore, the conveying speed of the conveyor belt is 0.1 to 5.0 m / min. The limitation of the conveying speed can better ensure that the lyocell fiber is transported in a stable and orderly manner, while completing the processes of laying, dehydration, chitosan solution spraying and squeezing, NaOH solution spraying and squeezing, washing, re-dehydration, sodium alginate solution spraying and squeezing, CaCl2 solution spraying and squeezing, and re-washing.
[0041] Furthermore, the product performance indicators of the antibacterial flame retardant lyocell fiber include: dry breaking strength ≥3.8cN / dtex, dry breaking elongation ≥12.0%, limiting oxygen index LOI>27%, Staphylococcus aureus inhibition rate ≥92%, Escherichia coli inhibition rate ≥92%, and Candida albicans inhibition rate ≥90%.
[0042] The second purpose of the technical scheme is to provide: a preparation system of antibacterial flame-retardant lyocell fiber, comprising a conveyor mesh belt and at least seven groups of pressure rollers distributed on the conveyor mesh, the conveyor mesh belt comprising a chitosan solution spraying section, a NaOH solution spraying section, a water spraying section I, a sodium alginate solution spraying section, a CaCl2 solution spraying section and a water spraying section II which are arranged in sequence, a group of pressure rollers for squeezing water are arranged at the front side of the station of the chitosan solution spraying section, and a pressure roller for squeezing water is arranged between the chitosan solution spraying section and the NaOH solution spraying section. A pressing roller for squeezing unabsorbed chitosan, a pressing roller for squeezing unreacted NaOH is provided between the NaOH solution spray section and the water spray section I, a pressing roller for squeezing water is provided between the water spray section I and the sodium alginate solution spray section, a pressing roller for squeezing unabsorbed sodium alginate is provided between the sodium alginate solution spray section and the CaCl2 solution spray section, a pressing roller for squeezing unreacted CaCl2 is provided between the CaCl2 solution spray section and the water spray section II, and a pressing roller for squeezing water is provided at the rear side of the station of the water spray section II;
[0043] In addition, a chitosan solution spraying device is provided above the station of the chitosan solution spraying section, a NaOH solution spraying device is provided above the station of the NaOH solution spraying section, a water spraying device I is provided above the station of the water spraying section I, a sodium alginate solution spraying device is provided above the station of the sodium alginate solution spraying section, a CaCl2 solution spraying device is provided above the station of the CaCl2 solution spraying section, and a water spraying device II is provided above the station of the water spraying section II.
[0044] Furthermore, the conveyor mesh belt is sleeved on a transmission roller to drive the conveyor mesh belt.
[0045] Furthermore, a roller for supporting the weight of the conveyor mesh belt and the lyocell fiber is provided on the lower side of the conveyor mesh belt to reduce mesh belt wear. Preferably, there are multiple rollers evenly distributed on the lower side of the conveyor mesh belt.
[0046] Furthermore, the lower side of the conveyor mesh belt is also provided with a tension roller for controlling the conveyor mesh belt. Preferably, there are two tension rollers, which are distributed at both ends of the lower side of the conveyor mesh belt.
[0047] Furthermore, a chitosan solution receiving tank is provided below the chitosan solution spraying section, and the chitosan solution receiving tank is connected to the chitosan solution spraying device to achieve effective collection and recycling of the chitosan solution;
[0048] A NaOH solution receiving tank is provided below the NaOH solution spraying section, and the NaOH solution receiving tank is connected to the NaOH solution spraying device to achieve effective collection and recycling of the NaOH solution;
[0049] A water receiving tank I is provided below the water spray section I, and the water receiving tank I is connected to the water spray device I to achieve effective water collection and recycling;
[0050] A sodium alginate solution receiving tank is provided below the sodium alginate solution spraying section, and the sodium alginate solution receiving tank is connected to the sodium alginate solution spraying device to achieve effective collection and recycling of the sodium alginate solution;
[0051] A CaCl2 solution receiving tank is provided below the CaCl2 solution spraying section, and the CaCl2 solution receiving tank is connected to the CaCl2 solution spraying device to achieve effective collection and recycling of the CaCl2 solution;
[0052] A water receiving tank II is provided below the water spraying section II, and the water receiving tank II is connected to the water spraying device II to realize the effective collection and recycling of water.
[0053] In this technical solution, the chemical reaction formulas / mechanisms involved include:
[0054] 1. Lyocell fiber production process: N-methylmorpholine-N-oxide monohydrate (NMMO) can combine with the hydroxyl groups on cellulose to form hydrogen bonds, and then dissolve the cellulose. The process includes: first, cellulose pulp is mixed with NMMO aqueous solution, and appropriate amounts of antioxidants, additives, etc. are added. Under vacuum, heating, and stirring, the cellulose gradually dissolves to form a spinning solution; secondly, the spinning solution is wet-spun by dry-jet spinning, and the spinning fine stream is solidified in a coagulation bath under a stretched state; finally, the fiber is post-treated by washing, oiling, drying, etc. to obtain Lyocell fiber;
[0055] Formation of chitosan solution: In acidic aqueous solution, the amino groups on the chitosan molecular chain are protonated to generate -NH3 + Ions cause the molecular chains to carry a large amount of positive charges. The molecular chains are evenly dispersed in the acidic aqueous solution through electrostatic repulsion, thereby achieving the dissolution of chitosan. Chitosan solution can be obtained by stirring.
[0056] Chitosan regeneration: Chitosan solution is placed in an alkaline coagulation bath (usually NaOH solution), protonated -NH3 + The ions will neutralize with -OH and reform the amino groups. In this way, the electrostatic interaction between the chitosan molecular chains disappears, and the molecular chains re-aggregate and precipitate, thus regenerating into a new shape.
[0057] Formation of sodium alginate solution: Sodium alginate itself is a water-soluble substance. After adding water, the alginate radical is negatively charged, and the sodium alginate molecular chain is evenly dispersed in the water through electrostatic repulsion. After stirring, a sodium alginate solution can be obtained;
[0058] Sodium alginate regeneration: Sodium alginate solution in Mg 2+ , Fe 3+ , Ca 2+ In aqueous solution containing ions, alginate ions react with Mg 2+ , Fe 3+ , Ca 2+ The ions undergo ionic cross-linking reaction to form water-insoluble calcium alginate, magnesium alginate, and iron alginate, thereby regenerating the shape.
[0059] In the present technical scheme, positional relationships such as "on", "in sequence", "front side of the workstation", "back side of the workstation", "between", "above the workstation", "lower side", "both ends", and "below" are defined according to the situations under actual usage conditions. They are conventional terms in this technical field and are also conventional terms used by technical personnel in this field in actual use.
[0060] The beneficial technical effects brought about by adopting this technical solution are:
[0061] 1. In the present invention, firstly, lyocell fiber (short fiber) is used as the base material, and chitosan is introduced to coat the lyocell fiber, so that the regenerated chitosan is wrapped on the surface of the lyocell fiber to form an antibacterial layer; secondly, sodium alginate is attached to the surface of chitosan through electrostatic self-assembly to form a flame retardant layer; finally, Ca2+ is used for cross-linking to obtain antibacterial and flame retardant lyocell fiber. Among them, chitosan and sodium alginate are coated on the surface of lyocell fiber. In fact, chitosan and sodium alginate are used as modifiers. Chitosan is positively charged and sodium alginate is negatively charged. Therefore, the coating cannot be carried out at the same time (once the two are mixed, they will cause gelation due to electrostatic interaction). They need to be carried out separately, and the electrostatic layer-by-layer self-assembly technology can be used to wrap the two oppositely charged substances layer by layer on the surface of lyocell fiber. Finally, not only the antibacterial property but also the flame retardant property of lyocell fiber is given. At the same time, the adhesion of the flame retardant layer is further strengthened, the water washing resistance of the functional fiber is improved, and the influence of water washing on the antibacterial and flame retardant properties of the functional fiber is weakened.
[0062] 2. The chitosan and sodium alginate raw materials used in the present invention are both natural polymers. By utilizing the antibacterial properties of chitosan and the flame retardant properties of calcium alginate, the good biocompatibility of the lyocell fiber itself can be retained to a great extent while imparting antibacterial and flame retardant properties to the fiber. The antibacterial and flame retardant lyocell staple fibers finally prepared have stronger biosafety and have broader application prospects in the textile field. In addition, the preparation method proposed in the present invention is mainly based on the post-treatment of lyocell fibers and does not affect the production process of the lyocell fibers themselves. This is greatly different from the preparation of existing functional spinning solutions, that is, the preparation method has great prospects for industrial application.
[0063] 3. In the present invention, spraying and roller squeezing are used to treat the lyocell fibers of the conveyor belt respectively. The operation method is simple and easy to operate, and the lyocell fibers are treated uniformly, with high treatment efficiency and low cost (compared with impregnation, the effect is obvious), which effectively ensures the sustainability and stability of the preparation process, and realizes the high efficiency and high quality of the preparation process of the antibacterial and flame-retardant lyocell fibers.
[0064] 4. In the present invention, the limitation of each spraying sequence can better guarantee the finished product indicators of the antibacterial and flame-retardant lyocell fiber (including strength, elongation, antibacterial and flame-retardant properties, etc.). For example, since the sodium alginate layer is the main source of imparting flame-retardant properties to the fiber, and the chitosan layer cannot impart good flame-retardant properties to the fiber, if a good flame-retardant effect is to be achieved, it is best to limit the outermost layer of the fiber to a sodium alginate layer; therefore, the present invention adopts the method of first forming a chitosan layer on the fiber surface, and then forming a sodium alginate layer on the surface of the chitosan layer, so that the sodium alginate layer with good flame-retardant effect is wrapped on the outermost surface of the fiber. BRIEF DESCRIPTION OF THE DRAWINGS
[0065] Figure 1 is a process flow chart of the present invention;
[0066] Figure 2 is an equipment layout diagram of the preparation system of the present invention;
[0067] In the figure, 1. conveying mesh belt, 2. chitosan solution spraying device, 3. NaOH solution spraying device, 4. water spraying device I, 5. sodium alginate solution spraying device, 6. CaCl2 solution spraying device, 7. water spraying device II, 8. pressure roller, 9. transmission roller, 10. tension roller, 11. chitosan solution receiving tank, 12. NaOH solution receiving tank, 13. water receiving tank I, 14. sodium alginate solution receiving tank, 15. CaCl2 solution receiving tank, 16. water receiving tank II, 17. roller. DETAILED DESCRIPTION
[0068] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0069] Example 1
[0070] This embodiment provides: a method for preparing antibacterial flame-retardant lyocell fiber, such as Figure 1 As shown, the specific steps are as follows:
[0071] 1) Preparation of Lyocell Fiber
[0072] The cellulose pulp is crushed and dissolved in an aqueous solution of N-methylmorpholine-N-oxide (NMMO) to form a cellulose solution with a concentration of 13.2 wt %; then, the cellulose solution is filtered and a lyocell fiber tow is obtained by dry-jet wet spinning;
[0073] The obtained lyocell fiber tow is washed with water, cut, and the lyocell fiber (short fiber) having a length of 38 mm, a dry breaking strength of ≥4.5 cN / dtex, and a dry breaking elongation of ≥18% is obtained;
[0074] 2) Laying net and dehydration
[0075] The obtained lyocell fibers are evenly spread on a stainless steel conveyor mesh belt, and then the lyocell fibers are squeezed and dehydrated by a pressing roller to obtain lyocell fibers with a water content of 50%;
[0076] 3) Spraying and squeezing of chitosan solution
[0077] A chitosan solution with a concentration of 1.0 wt% and a temperature of 25° C. is added to a chitosan solution spraying device to spray the lyocell fibers on the stainless steel conveyor mesh belt; then, a pressing roller is used to squeeze the lyocell fibers to remove the unabsorbed chitosan (the chitosan solution squeezed by the pressing roller is recovered and recycled through a receiving tank), and the lyocell fibers with a chitosan solution content of 50% are obtained;
[0078] 4) NaOH solution spraying and squeezing
[0079] A NaOH solution with a concentration of 0.5wt% and a temperature of 25°C is added to a NaOH solution spraying device to spray the Lyocell fibers on the stainless steel conveyor mesh belt; then, a pressure roller is used to squeeze the Lyocell fibers to remove unreacted NaOH (the NaOH solution squeezed by the pressure roller is recovered and recycled through a receiving tank), and the NaOH solution content is controlled to be 350% of the Lyocell fibers;
[0080] 5) Washing and dehydration
[0081] The lyocell fibers on the stainless steel conveyor mesh belt are sprayed with water by the water spray device I, that is, the lyocell fibers are washed with water to remove the unreacted NaOH remaining on the surface of the lyocell fibers; then, the lyocell fibers are squeezed and dehydrated to obtain lyocell fibers with a water content of 50%;
[0082] 6) Sodium alginate solution spraying and squeezing
[0083] A sodium alginate solution with a concentration of 1.0wt% and a temperature of 45°C is added to a sodium alginate solution spraying device to spray the lyocell fibers on the stainless steel conveyor mesh belt; then, a pressing roller is used to squeeze the lyocell fibers to remove the unabsorbed sodium alginate (the sodium alginate solution squeezed by the pressing roller is recovered and recycled through a receiving tank), and the lyocell fibers with a sodium alginate solution content of 50% are obtained;
[0084] 7) CaCl2 solution spraying and squeezing
[0085] A CaCl2 solution with a concentration of 0.5wt% and a temperature of 25°C is added to a CaCl2 solution spraying device to spray the Lyocell fibers on the stainless steel conveyor mesh belt; then, a pressing roller is used to squeeze the Lyocell fibers to remove unreacted CaCl2 (the CaCl2 solution squeezed by the pressing roller is recovered and recycled through a receiving tank), and the CaCl2 solution content is controlled to be 50% of the Lyocell fibers;
[0086] 8) Wash again
[0087] The lyocell fibers on the stainless steel conveyor belt are sprayed by the water spray device II, i.e., the lyocell fibers are washed with water to remove the unreacted CaCl2 remaining on the surface of the lyocell fibers; then, the lyocell fibers are squeezed and dehydrated to control the water content of the lyocell fibers to be 50%, thus obtaining an antibacterial and flame-retardant lyocell fiber product, which is recorded as C1.
[0088] Among them, the conveying speed of the stainless steel conveyor mesh belt is 2.0m / min.
[0089] Example 2
[0090] The present embodiment is different from the embodiment 1 in that a chitosan solution with a concentration of 0.5 wt % is used for spraying, and the rest is the same as the embodiment 1. Finally, an antibacterial and flame-retardant lyocell fiber product is obtained, which is recorded as C2.
[0091] Example 3
[0092] The present embodiment is different from the embodiment 1 in that a chitosan solution with a concentration of 2.0 wt% is used for spraying, and the rest is the same as the embodiment 1. Finally, an antibacterial and flame-retardant lyocell fiber product is obtained, which is recorded as C3.
[0093] Example 4
[0094] The present embodiment is different from the embodiment 1 in that a sodium alginate solution with a concentration of 0.5 wt % is used for spraying, and the rest is the same as the embodiment 1. Finally, an antibacterial and flame-retardant lyocell fiber product is obtained, which is recorded as C4.
[0095] Example 5
[0096] The present embodiment is different from the embodiment 1 in that a sodium alginate solution with a concentration of 2.0 wt% is used for spraying, and the rest is the same as the embodiment 1. Finally, an antibacterial and flame-retardant lyocell fiber product is obtained, which is recorded as C5.
[0097] Example 6
[0098] The present embodiment is different from the embodiment 1 in that a chitosan solution with a concentration of 0.5wt% and a sodium alginate solution with a concentration of 0.5wt% are used for spraying respectively, and the rest is the same as the embodiment 1. Finally, an antibacterial and flame-retardant lyocell fiber product is obtained, which is recorded as C6.
[0099] Example 7
[0100] The present embodiment is different from the embodiment 1 in that a chitosan solution with a concentration of 2.0wt% and a sodium alginate solution with a concentration of 2.0wt% are used for spraying respectively, and the rest is the same as the embodiment 1. Finally, an antibacterial and flame-retardant lyocell fiber product is obtained, which is recorded as C7.
[0101] Comparative Example 1
[0102] The present comparative example is different from Example 1 in that the lyocell fiber is not sprayed or squeezed with the chitosan solution and the NaOH solution, that is, no antibacterial layer is formed on the surface of the lyocell fiber. The rest is the same as Example 1. Finally, a lyocell fiber reference product is obtained, which is recorded as D1.
[0103] Comparative Example 2
[0104] The present comparative example is different from Example 1 in that the lyocell fiber is not sprayed or squeezed with the sodium alginate solution and the CaCl2 solution, that is, no flame retardant layer is formed on the surface of the lyocell fiber. The rest is the same as Example 1. Finally, a lyocell fiber reference product is obtained, which is recorded as D2.
[0105] Comparative Example 3
[0106] The difference between this comparative example and Example 1 is that: a chitosan solution with a concentration of 0.1wt% and a sodium alginate solution with a concentration of 0.1wt% are used for corresponding spraying respectively, and the rest is the same as Example 1. Finally, a lyocell fiber reference product is obtained, which is recorded as D3.
[0107] Comparative Example 4
[0108] The difference between this comparative example and Example 1 is that: a chitosan solution with a concentration of 3.0wt% and a sodium alginate solution with a concentration of 3.0wt% are used for corresponding spraying respectively, and the rest is the same as Example 1. Finally, a lyocell fiber reference product is obtained, which is recorded as D4.
[0109] Comparative Example 5
[0110] Compared with Example 1, the difference between this comparative example and this comparative example is that: the lyocell fiber is firstly sprayed and squeezed with corresponding sodium alginate solution and CaCl2 solution, that is, a flame retardant layer is first formed on the surface of the lyocell fiber; and then the lyocell fiber is sprayed and squeezed with corresponding chitosan solution and NaOH solution, that is, an antibacterial layer is formed on the surface of the flame retardant layer. The rest is the same as Example 1. Finally, a lyocell fiber control product is obtained, which is recorded as D5.
[0111] The products C1-C7 and D1-D5 obtained by the above-mentioned Examples 1-7 and Comparative Examples 1-5 were subjected to linear density test, mechanical property test, flame retardant property test and antibacterial property test, respectively, and the test conditions were kept consistent. Each product was tested 10 times and the average value was taken. The results are shown in Tables 1-3 below.
[0112] Table 1 shows the test results of linear density and mechanical properties of the corresponding products
[0113]
[0114]
[0115] Table 2 shows the flame retardant performance test results of the corresponding products
[0116]
[0117] Table 3 shows the antibacterial performance test results of the corresponding products
[0118]
[0119]
[0120] From the performance test results in Table 1-3, we can draw the following conclusions:
[0121] 1. By comparing Examples 1-3, it can be concluded that the concentration of the chitosan solution has a great influence on the antibacterial properties of the final Lyocell fiber product. The higher the concentration of the chitosan solution, the better the antibacterial properties of the final Lyocell fiber product; however, the concentration of the chitosan solution has no significant effect on the flame retardant properties of the final Lyocell fiber product, indicating that the antibacterial properties of the final Lyocell fiber product mainly come from the antibacterial layer formed by chitosan;
[0122] 2. Comparing Examples 1, 4-5, it can be concluded that the concentration of sodium alginate solution has a great influence on the flame retardant properties of the final Lyocell fiber product. The higher the concentration of sodium alginate solution, the better the flame retardant properties of the final Lyocell fiber product; however, the concentration of sodium alginate solution has no significant effect on the antibacterial properties of the final Lyocell fiber product, indicating that the flame retardant properties of the final Lyocell fiber product mainly come from the flame retardant layer formed by sodium alginate;
[0123] 3. Comparative Examples 1-7 and Comparative Examples 3-4 show that the concentrations of chitosan solution and sodium alginate solution will have a certain impact on the linear density and mechanical properties of the Lyocell fiber final product. When the concentrations of chitosan solution and sodium alginate solution are too low (Comparative Example 3), the antibacterial layer and flame retardant layer formed on the surface of the Lyocell fiber final product are relatively thin. Although the linear density and mechanical properties of the Lyocell fiber final product are slightly affected, the flame retardant and antibacterial properties of the Lyocell fiber final product will be significantly reduced; when the concentrations of chitosan solution and sodium alginate solution are too high (Comparative Example 4), although the flame retardant and antibacterial properties of the Lyocell fiber final product will be greatly improved, the antibacterial layer and flame retardant layer formed on the surface of the Lyocell fiber final product are relatively thick, resulting in a significant increase in the linear density and linear density deviation rate of the Lyocell fiber final product, which is likely to cause the Lyocell fiber final product to be uneven in thickness, and the mechanical properties (dry breaking strength and dry breaking elongation) will also be significantly reduced. Therefore, only when the concentrations of the chitosan solution and the sodium alginate solution are within a certain range (i.e., 0.5-2.0wt%, including Examples 1-7), the prepared lyocell fiber final product not only has good flame retardant properties (limiting oxygen index LOI>27%) and antibacterial properties (Staphylococcus aureus inhibition rate ≥92%, Escherichia coli inhibition rate ≥92%, Candida albicans inhibition rate ≥90%), but also does not cause a significant increase in fiber linear density, nor does it cause a significant decrease in fiber dry breaking strength and dry breaking elongation, etc.;
[0124] 4. By comparing Example 1 with Comparative Example 1, it can be concluded that if chitosan does not form an antibacterial layer on the surface of the lyocell fiber (Comparative Example 1), the lyocell fiber will not have good antibacterial properties. Although the fiber has good flame retardant properties (limiting oxygen index LOI = 32%) at the beginning, after 20 water washings, the flame retardant properties drop significantly (limiting oxygen index LOI = 23% < 27%), and it cannot reach the level of flame retardant materials; if chitosan forms an antibacterial layer on the fiber surface (Example 1), and then forms a flame retardant layer on the surface of the antibacterial layer, even after 20 water washings, the fiber still has good flame retardant properties (limiting oxygen index LOI = 30%), indicating that the antibacterial layer formed by chitosan on the fiber surface can not only provide good antibacterial properties for the fiber, but also help maintain the flame retardant properties of the fiber. This is because the electrostatic interaction between the antibacterial layer formed by chitosan and the flame retardant layer formed by sodium alginate further strengthens the adhesion of the flame retardant layer, improves the water washing resistance of the fiber, and weakens the effect of water washing on the flame retardant properties of the fiber;
[0125] 5. By comparing Example 1 and Example 2, it can be concluded that if sodium alginate does not form a flame retardant layer on the surface of the antibacterial layer of the lyocell fiber (Comparative Example 2), the fiber will not have good flame retardant properties (Limiting Oxygen Index LOI = 20%). Although the fiber has good antibacterial properties at the beginning (Staphylococcus aureus inhibition rate = 98%, Escherichia coli inhibition rate = 97%, Candida albicans inhibition rate = 94%), but after 20 times of washing, the fiber antibacterial properties will decrease to a certain extent (Staphylococcus aureus inhibition rate = 91%, Escherichia coli inhibition rate = 90%, Candida albicans inhibition rate = 89%); and if a flame retardant layer is formed on the surface of the fiber antibacterial layer (Example 1), even after 20 times of washing, the antibacterial properties of the fiber will not decrease significantly (Staphylococcus aureus inhibition rate = 91%, Escherichia coli inhibition rate = 90%, Candida albicans inhibition rate = 89%). The antibacterial rate of Staphylococcus aureus = 95%, the antibacterial rate of Escherichia coli = 96%, and the antibacterial rate of Candida albicans = 95%) indicates that the flame retardant layer formed on the surface of the fiber antibacterial layer can not only provide good flame retardant properties for the fiber, but also help maintain the antibacterial properties of the fiber. This is because the electrostatic interaction between the antibacterial layer formed by chitosan and the flame retardant layer formed by sodium alginate not only strengthens the adhesion of the flame retardant layer, but also strengthens the firmness of the antibacterial layer, improves the water washing resistance of the fiber, and weakens the effect of water washing on the antibacterial properties of the fiber.
[0126] VI. By comparing Example 1 with Comparative Example 5, it can be concluded that: if the spraying order of the chitosan solution and the sodium alginate solution is changed (Example 4), that is, a sodium alginate flame retardant layer is first formed on the fiber surface, and then a chitosan antibacterial layer is formed on the surface of the flame retardant layer, this will not have a significant effect on the linear density and mechanical properties of the fiber, and the antibacterial property of the fiber will not be significantly reduced (Staphylococcus aureus inhibition rate = 98%, Escherichia coli inhibition rate = 98%, Candida albicans inhibition rate = 96%), and after 20 times of water washing, it still has good antibacterial property (Staphylococcus aureus inhibition rate = 95%, Escherichia coli inhibition rate = 95%, Candida albicans inhibition rate = 95%), but the flame retardant property of the fiber has decreased to a certain extent, and the limiting oxygen index LOI has decreased from 32% to 29%, resulting in that after 20 times of water washing, the flame retardant property of the fiber can barely reach the level of flame retardant materials (limiting oxygen index LOI = 27%). Therefore, although the order in which the flame retardant layer and the antibacterial layer are formed on the fiber surface has no significant effect on the fiber's linear density, mechanical properties and antibacterial properties, it will have a certain impact on the fiber's flame retardant properties. In order to enable the fiber to have a better flame retardant effect, it is preferred to first form the antibacterial layer on the fiber surface and then form the flame retardant layer on the surface of the antibacterial layer.
[0127] Example 8
[0128] On the basis of Examples 1-7, in order to better cooperate with the preparation process of antibacterial flame-retardant lyocell fiber, this example proposes a preparation system with strong adaptability and good stability of the preparation process, such as Figure 2 As shown, the details are as follows:
[0129] A preparation system of antibacterial flame-retardant lyocell fiber comprises a conveyor mesh belt 1 and at least seven groups of pressing rollers 8 distributed on the conveyor mesh belt 1, wherein the conveyor mesh belt 1 comprises a chitosan solution spraying section, a NaOH solution spraying section, a water spraying section I, a sodium alginate solution spraying section, a CaCl2 solution spraying section and a water spraying section II which are arranged in sequence, a pressing roller 8 for squeezing water is arranged at the front side of the station of the chitosan solution spraying section, a pressing roller 8 for squeezing unabsorbed chitosan is arranged between the chitosan solution spraying section and the NaOH solution spraying section, a pressing roller 8 for squeezing unreacted NaOH is arranged between the NaOH solution spraying section and the water spraying section I, a pressing roller 8 for squeezing water is arranged between the water spraying section I and the sodium alginate solution spraying section, and a pressing roller 8 for squeezing water is arranged between the sodium alginate solution spraying section and the CaCl2 solution spraying section. A pressing roller 8 for squeezing unabsorbed sodium alginate is provided between the aCl2 solution spraying sections, a pressing roller 8 for squeezing unreacted CaCl2 is provided between the CaCl2 solution spraying section and the water spraying section II, and a pressing roller 8 for squeezing water is provided at the rear side of the station of the water spraying section II; and, a chitosan solution spraying device 2 is provided above the station of the chitosan solution spraying section, a NaOH solution spraying device 3 is provided above the station of the NaOH solution spraying section, a water spraying device I4 is provided above the station of the water spraying section I, a sodium alginate solution spraying device 5 is provided above the station of the sodium alginate solution spraying section, a CaCl2 solution spraying device 6 is provided above the station of the CaCl2 solution spraying section, and a water spraying device II7 is provided above the station of the water spraying section II.
[0130] Among them, a stainless steel conveyor mesh belt 1 can be used, and the arrangement of the conveyor mesh belt 1 is further defined as follows: the conveyor mesh belt 1 is sleeved on the transmission roller 9 to drive the transmission of the conveyor mesh belt 1. A roller 17 for supporting the weight of the conveyor mesh belt 1 and the lyocell fiber is provided on the lower side of the conveyor mesh belt 1 to reduce the wear of the mesh belt. Preferably, there are multiple rollers 17, which are evenly distributed on the lower side of the conveyor mesh belt 1. And, a tension roller 10 for controlling the conveyor mesh belt 1 is also provided on the lower side of the conveyor mesh belt 1. Preferably, there are two tension rollers 10, which are distributed at both ends of the lower side of the conveyor mesh belt 1.
[0131] In order to ensure the stable working condition of the antibacterial flame retardant lyocell fiber production line and realize the circulation, recycling and reuse of the spray liquid, further restrictions are imposed:
[0132] A chitosan solution receiving tank 11 is provided below the chitosan solution spraying section, and the chitosan solution receiving tank 11 is connected to the chitosan solution spraying device 2 to achieve effective collection and recycling of the chitosan solution; a NaOH solution receiving tank 12 is provided below the NaOH solution spraying section, and the NaOH solution receiving tank 12 is connected to the NaOH solution spraying device 3 to achieve effective collection and recycling of the NaOH solution; a water receiving tank Ⅰ 13 is provided below the water spraying section Ⅰ, and the water receiving tank Ⅰ 13 is connected to the water spraying device Ⅰ 4 to achieve effective collection and recycling of water; alginate solution A sodium alginate solution receiving tank 14 is provided below the liquid spraying section, and the sodium alginate solution receiving tank 14 is connected to the sodium alginate solution spraying device 5 to achieve effective collection and recycling of the sodium alginate solution; a CaCl2 solution receiving tank 15 is provided below the CaCl2 solution spraying section, and the CaCl2 solution receiving tank 15 is connected to the CaCl2 solution spraying device 6 to achieve effective collection and recycling of the CaCl2 solution; a water receiving tank II 16 is provided below the water spraying section II, and the water receiving tank II 16 is connected to the water spraying device II 7 to achieve effective collection and recycling of water.
[0133] In addition, for each device involved in this preparation system:
[0134] Conveyor mesh belt 1: Specifically, a stainless steel conveyor mesh belt 1 can be used for laying and transmitting lyocell fibers;
[0135] Chitosan solution spraying device 2: used to spray the prepared chitosan solution into the lyocell fiber, so that the chitosan solution is evenly wrapped on the surface of the lyocell fiber;
[0136] NaOH solution spraying device 3: used for spraying the prepared NaOH solution into the lyocell fiber to solidify the chitosan solution evenly wrapped on the surface of the lyocell fiber, thereby forming an antibacterial layer on the fiber surface;
[0137] Water spray device Ⅰ4: used for washing and removing the unreacted NaOH solution on the fiber surface;
[0138] Sodium alginate solution spraying device 5: used to spray the prepared sodium alginate solution into the lyocell fiber, so that the sodium alginate solution is evenly wrapped on the surface of the lyocell fiber;
[0139] CaCl2 solution spraying device 6: used to spray the prepared CaCl2 solution into the lyocell fiber. 2+ Used to cross-link the sodium alginate solution uniformly wrapped on the surface of the lyocell fiber to solidify it, thereby forming a flame retardant layer;
[0140] Water spray device II7: used for washing and removing the unreacted CaCl2 solution on the fiber surface;
[0141] Pressing roller 8: used for squeezing and removing excess chitosan solution, NaOH solution, sodium alginate solution, CaCl2 solution and water;
[0142] Transmission roller 9: used for transmission of the mesh belt 1;
[0143] Tension roller 10: used to control the tension of the conveyor belt 1;
[0144] Chitosan solution receiving tank 11: used for recovering the chitosan solution squeezed out by the pressing roller 8;
[0145] NaOH solution receiving tank 12: used to recover the NaOH solution squeezed out by the pressing roller 8;
[0146] Water receiving tank I 13: used to recover the washing water containing NaOH squeezed out by the pressing roller 8;
[0147] Sodium alginate solution receiving tank 14: used for recovering the sodium alginate solution squeezed out by the pressing roller 8;
[0148] CaCl2 solution receiving tank 15: used to recover the CaCl2 solution squeezed out by the pressing roller 8;
[0149] Water receiving tank II 16: used to recover the washing water containing CaCl2 squeezed out by the pressing roller 8;
[0150] Roller 17: used to support the weight of the conveyor mesh belt 1 and the lyocell fiber, and reduce the wear of the conveyor mesh belt 1.
[0151] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described with reference to the above embodiment, it is still possible for a person skilled in the art to modify the technical solutions described in the above embodiment or to replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing antibacterial flame-retardant lyocell fiber, characterized in that: The steps include: S1: Pre-treatment The lyocell fibers are evenly spread on a conveyor mesh belt, and the lyocell fibers are squeezed by a pressing roller to obtain lyocell fibers with a water content of 30 to 50%; S2: Chitosan solution spraying and squeezing The chitosan solution is sprayed on the lyocell fiber on the conveyor mesh belt, and the lyocell fiber is squeezed by a pressing roller to obtain the lyocell fiber with a chitosan solution content of 50-60%. S3: NaOH solution spraying, squeezing The NaOH solution is sprayed on the lyocell fiber on the conveyor mesh belt, and the lyocell fiber is squeezed by a pressing roller to obtain the lyocell fiber with a NaOH solution content of 30-50%; S4: Washing and dehydration The lyocell fibers on the conveyor belt are sprayed with water, and the lyocell fibers are squeezed by a pressing roller to obtain lyocell fibers with a water content of 30-50%. S5: Sodium alginate solution spraying and squeezing The sodium alginate solution is sprayed on the lyocell fiber on the conveyor belt, and the lyocell fiber is squeezed by a pressing roller to obtain the lyocell fiber with a sodium alginate solution content of 50-60%. S6: CaCl2 solution spraying, squeezing The Lyocell fibers on the conveyor belt are sprayed with a CaCl2 solution, and the Lyocell fibers are squeezed by a pressing roller to obtain Lyocell fibers with a CaCl2 solution content of 30-50%. S7: Post-processing The antibacterial and flame-retardant lyocell fibers are obtained by spraying lyocell fibers on a conveyor belt with water and squeezing the lyocell fibers through a pressing roller.
2. The method for preparing the antibacterial flame-retardant lyocell fiber according to claim 1, characterized in that: The method for preparing the antibacterial flame-retardant lyocell fiber also includes the preparation of the lyocell fiber, which is specifically as follows: The cellulose pulp is crushed and dissolved in an aqueous solution of N-methylmorpholine-N-oxide to form a cellulose solution with a concentration of 12.0 to 14.0 wt %; then, the cellulose solution is filtered and subjected to dry-jet wet spinning to obtain a lyocell fiber tow; The obtained lyocell fiber tow is washed with water and cut to obtain lyocell fibers with a length of 30 to 60 mm, a dry breaking strength of ≥4.5 cN / dtex and a dry breaking elongation of ≥18%.
3. The method for preparing the antibacterial flame-retardant lyocell fiber according to claim 1, characterized in that: In step S2, the concentration of the chitosan solution is 0.5-2.0 wt%, and the temperature of the chitosan solution is 20-50°C.
4. The method for preparing the antibacterial flame-retardant lyocell fiber according to claim 1, characterized in that: In step S3, the concentration of the NaOH solution is 0.1-1.0 wt%, and the temperature of the NaOH solution is 20-30°C.
5. The method for preparing the antibacterial flame-retardant lyocell fiber according to claim 1, characterized in that: In step S5, the concentration of the sodium alginate solution is 0.5-2.0 wt %, and the temperature of the sodium alginate solution is 40-50° C.
6. The method for preparing the antibacterial flame-retardant lyocell fiber according to claim 1, characterized in that: In step S6, the concentration of the CaCl2 solution is 0.1-1.0 wt%, and the temperature of the CaCl2 solution is 20-30°C.
7. The method for preparing the antibacterial flame-retardant lyocell fiber according to claim 1, characterized in that: The product performance indicators of the antibacterial flame-retardant lyocell fiber include: dry breaking strength ≥3.8 cN / dtex, dry breaking elongation ≥12.0%, limiting oxygen index LOI>27%, Staphylococcus aureus inhibition rate ≥92%, Escherichia coli inhibition rate ≥92%, and Candida albicans inhibition rate ≥90%.
8. A system for preparing antibacterial flame-retardant lyocell fiber, characterized in that: The preparation method according to any one of claims 1 to 7 adopts the preparation system, the preparation system comprising a conveyor mesh belt (1) and at least seven groups of pressure rollers (8) distributed on the conveyor mesh; The conveyor mesh belt (1) comprises a chitosan solution spraying section, a NaOH solution spraying section, a water spraying section I, a sodium alginate solution spraying section, a CaCl2 solution spraying section and a water spraying section II which are arranged in sequence, a pressure roller (8) for squeezing water is provided at the front side of the station of the chitosan solution spraying section, a pressure roller (8) for squeezing unabsorbed chitosan is provided between the chitosan solution spraying section and the NaOH solution spraying section, a pressure roller (8) for squeezing unreacted NaOH is provided between the NaOH solution spraying section and the water spraying section I, a pressure roller (8) for squeezing water is provided between the water spraying section I and the sodium alginate solution spraying section, a pressure roller (8) for squeezing unabsorbed sodium alginate is provided between the sodium alginate solution spraying section and the CaCl2 solution spraying section, a pressure roller (8) for squeezing unreacted CaCl2 is provided between the CaCl2 solution spraying section and the water spraying section II, and a pressure roller (8) for squeezing water is provided at the rear side of the station of the water spraying section II; A chitosan solution spraying device (2) is provided above the station of the chitosan solution spraying section, a NaOH solution spraying device (3) is provided above the station of the NaOH solution spraying section, a water spraying device I (4) is provided above the station of the water spraying section I, a sodium alginate solution spraying device (5) is provided above the station of the sodium alginate solution spraying section, a CaCl2 solution spraying device (6) is provided above the station of the CaCl2 solution spraying section, and a water spraying device II (7) is provided above the station of the water spraying section II.
9. The system for preparing the antibacterial flame-retardant lyocell fiber according to claim 8, characterized in that: The conveyor mesh belt (1) is sleeved on a driving roller (9), a support roller (17) for supporting the weight of the conveyor mesh belt (1) and the lyocell fiber is provided on the lower side of the conveyor mesh belt (1), and a tension roller (10) for controlling the conveyor mesh belt (1) is also provided on the lower side of the conveyor mesh belt (1).
10. The system for preparing antibacterial flame-retardant lyocell fiber according to claim 9, characterized in that: A chitosan solution receiving tank (11) is provided below the chitosan solution spraying section, and the chitosan solution receiving tank (11) is connected to the chitosan solution spraying device (2); A NaOH solution receiving tank (12) is provided below the NaOH solution spraying section, and the NaOH solution receiving tank (12) is connected to the NaOH solution spraying device (3); A water receiving tank I (13) is provided below the water spray section I, and the water receiving tank I (13) is connected to the water spray device I (4); A sodium alginate solution receiving tank (14) is provided below the sodium alginate solution spraying section, and the sodium alginate solution receiving tank (14) is connected to the sodium alginate solution spraying device (5); A CaCl2 solution receiving tank (15) is provided below the CaCl2 solution spraying section, and the CaCl2 solution receiving tank (15) is connected to the CaCl2 solution spraying device (6); A water receiving tank II (16) is provided below the water spraying section II, and the water receiving tank II is connected to the water spraying device II (7).
Citation Information
Patent Citations
Aftertreatment based preparation method for Lyocell cellulose fibers
CN109162096A
Preparation method for durable antibacterial cellulose fibres
CN109440450A
Sodium alginate / chitosan composite fiber and preparation method and application thereof
CN112410931A
Cited By
Blended yarn and preparation method thereof
CN120465158A
Renewable fiber cotton and preparation method thereof
CN120719404A